Rituximab in relapsed/refractory antineutrophil cytoplasmic antibody associated vasculitis: A single-center prospective observational study - Ekbote Gayatri; Tanna Dhaval; Negalur Natasha; Bindroo Muzaffar; Raval Dhiren; Sharma Lucky; Rajiva Gupta (Indian Journal of Rheumatology)
Background: Induction with cyclophosphamide (CYC) and glucocorticoids in antineutrophil cytoplasmic antibody-associated vasculitis (AAV) has a relapse of 30%–50%. Studies show that rituximab (RTX) is superior to CYC in refractory/relapsed AAV. We prospectively analyzed efficacy and safety of RTX in CYC-failed cases of AAV. Methods: Patients with AAV who relapsed or were refractory to CYC therapy were given RTX 1 gm at 0 and 15 days, followed by maintenance with 500 mg every 4–6 months. All patients received oral prednisolone. Disease activity was defined by Birmingham Vasculitis Activity Score/Wegener's granulomatosis (BVAS/WG). Remission was defined by the European League Against Rheumatism criteria. Results: From August 2012 to July 2018, 67 patients with AAV were seen at our center; 21 patients who relapsed after inductions with CYC or were refractory to CYC received RTX; 8 (38%) were refractory and 13 (62%) were relapsed AAV; 20 were anti-proteinase 3 positive and 1 was anti-myeloperoxidase positive. All were granulomatosis with polyangiitis (GPA). Mean time to relapse was 12.04 ± 7.8 months. Most common indication for RTX was lung followed by ophthalmic, renal, ear nose throat, and nervous system involvement. Median follow-up after induction with RTX was 24 months. Mean BVAS/WG was 11.2 at baseline, 0.66 at the end of 3 months, 0.16 at the end of 6 months, and remained stable at that value at 18 months. At 24 months, 16 patients (76.19%) remained in remission. One was refractory to RTX treatment even after 2 years. Two patients died and two were still under follow-up. Conclusion: In our experience, RTX is a good induction and maintenance strategy for relapsed/refractory AAV.